University Reforms in Central America: the influence of Rudolph Atcon - Murillo Lizardo, Orlando David; Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This work presents the influence that Rudolph Atcon had on the university reforms in Central America, mainly at the Universidad Nacional Autónoma de Honduras (UNAH) in the Republic of Honduras, during the sixties. Originality/contribution: It focuses on describing Atcon's technical proposal for the Honduran University and the Central America region, as a practical example of the promotion of the U.S. university model in Latin America and the Caribbean, especially in the 1960s and 1970s. Method: It is framed in the social history of education. Strategies / information collection: It is based on the analysis of documents from the historical and newspaper archives of the UNAH and the institutional archive of the Consejo Superior Universitario Centroamericano (CSUCA). A brief literature review was also carried out. Conclusions: University reforms in Central America during the sixties were intervened by U.S. agencies with the intention of stopping the influence of the Soviet Union in the region; therefore, the reform of the UNAH in our period of study was the result of the implementation of two antagonistic models: the Cordoba model of 18 and the U.S. model.